2017
DOI: 10.3390/met7100450
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Different Finite Element Methods in the Thermal Analysis of Friction Stir Welding (FSW)

Abstract: Friction Stir Welding (FSW) is a novel kind of welding for joining metals that are impossible or difficult to weld by conventional methods. Three-dimensional nature of FSW makes the experimental investigation more complex. Moreover, experimental observations are often costly and time consuming, and usually there is an inaccuracy in measuring the data during experimental tests. Thus, Finite Element Methods (FEMs) has been employed to overcome the complexity, to increase the accuracy and also to reduce costs. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 102 publications
(110 reference statements)
1
28
0
Order By: Relevance
“…The second phase however, shows a linear pattern. The same contour pattern for the stress-strain curve was also obtain in the literature which show a good agreement between the results of this study and the literature [17].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The second phase however, shows a linear pattern. The same contour pattern for the stress-strain curve was also obtain in the literature which show a good agreement between the results of this study and the literature [17].…”
Section: Resultssupporting
confidence: 90%
“…Higher deformation counter also observed in sample 1 due to the lower pore space in the model. The observed deformation in the literature is lower, because the thickness of the samples in the literature is more than the thickness of the specimens employed in this research [17]. Moreover, higher deformation in the horizontal axis was observed in the sample 1.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…As a function of temperature, the friction coefficient values in a variety of 0.207089 to 0.00058 are applied to the model [15,16]. Past studies claimed that, the welding rotational and transverse velocities affect the heat generation during process [1,[17][18][19]. The results of the paper indicated that the model in which the temperature dependent Young's modulus values are applied is more accurate.…”
Section: Methodsmentioning
confidence: 99%
“…As the tool plunges into the plates (while it is rotating) and moves along the welding seam, friction stir welding (FSW) will be created, Figure 1 [1]. Fundamentally, because of the large plastic deformation and the complicated frictional phenomena thermal and mechanical behaviors of friction stir welding are highly complex.…”
Section: Introductionmentioning
confidence: 99%